Place-based education & critical pedagogies of place: teachers challenging the neocolonizing processes of the New Zealand and Canadian schooling systems. - Harasymchuk, Brad (University of Canterbury. School of Teacher Education, 2015)
This international research set out to exemplify the pedagogical practices of 11 teachers from Christchurch/Ōtautahi, New Zealand (Aotearoa) and Saskatoon, Canada. It explores their resistance to the various colonial and neocolonizing constructs central to contemporary mainstream schooling in both cities (due to forces such as neoliberalism). These acts of resistance were the result of contesting ideologies of time, space, curriculum and assessment. The research, therefore, describes some of the pedagogical practises of these teachers. It also considers their narratives about their usage of place-based education (PBE) approaches and their commitment to the adoption of critical pedagogies of place (CPP) to meet the real needs of their students (both Indigenous and non-Indigenous). An interpretive paradigm was employed within a qualitative framework to underpin this research. A case study approach was also adopted and informed by a bricolage methodological framework. Primary and secondary data were collected from a number of storage sites (libraries) in both countries and through a questionnaire, interview and observation of each teacher’s classroom space. The data was analysed by coding key information while drawing out any recurring themes and points of difference. The findings reveal that certain aspects of PBE and CPP are accessible to teachers despite their feelings of being confined in terms of their ability to use time, space, curriculum and assessment within their traditional school institutions. Although their abilities to engage with PBE and CPP were limited, those teachers that had more control over time, space, curriculum and assessment were able to dive deeper into PBE and especially CPP. A key finding of this research was the extent of awareness and engagement that the teachers had in transforming controlled, static, spaces found in the classrooms, communities and natural environments into meaningful places with students. This finding also suggests that teachers with more control over time, space, ...